Enlarging the gene-geography of Europe and the Mediterranean area to STR loci of common forensic use: longitudinal and latitudinal frequency gradients - Messina, Francesco; Finocchio, Andrea; Akar, Nejat; Loutradis, Aphrodite; Michalodimitrakis, Emmanuel I; Brdicka, Radim; Jodice, Carla; Novelletto, Andrea (Annals of human biology, 2018)
BACKGROUND: Tetranucleotide Short Tandem Repeats (STRs) for human identification and common use in forensic cases have recently been used to address the population genetics of the North-Eastern Mediterranean area. However, to gain confidence in the inferences made using STRs, this kind of analysis should be challenged with changes in three main aspects of the data, i.e. the sizes of the samples, their distance across space and the genetic background from which they are drawn. AIM: To test the resilience of the gradients previously detected in the North-Eastern Mediterranean to the enlargement of the surveyed area and population set, using revised data. SUBJECTS AND METHODS: STR genotype profiles were obtained from a publicly available database (PopAffilietor databank) and a dataset was assembled including >7000 subjects from the Arabian Peninsula to Scandinavia, genotyped at eight loci. Spatial principal component analysis (sPCA) was applied and the frequency maps of the nine alleles which contributed most strongly to sPC1 were examined in detail. RESULTS: By far the greatest part of diversity was summarised by a single spatial principal component (sPC1), oriented along a SouthEast-to-NorthWest axis. The alleles with the top 5% squared loadings were TH01(9.3), D19S433(14), TH01(6), D19S433(15.2), FGA(20), FGA(24), D3S1358(14), FGA(21) and D2S1338(19). These results confirm a clinal pattern over the whole range for at least four loci (TH01, D19S433, FGA, D3S1358). CONCLUSIONS: Four of the eight STR loci (or even alleles) considered here can reproducibly capture continental arrangements of diversity. This would, in principle, allow for the exploitation of forensic data to clarify important aspects in the formation of local gene pools.
Keywords: Střední východ; Microsatellite Repeats; frekvence genu; mikrosatelitní repetice; Middle East; severní Afrika; genotyp; Gene Frequency; Středomoří; genetická variace; populační genetika; Genetics, Population; Africa, Northern; Genotype; Mediterranean Region; Genetic Variation